2022
DOI: 10.3390/nu14061217
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Chaste Weed and Its Components, Apigenin and Galangin, Affect Proliferation and Oxidative Stress in Blue Light-Irradiated HaCaT Cells

Abstract: While harmful effects of blue light on skin cells have been recently reported, there are few studies regarding natural products that alleviate its negative effects. Therefore, we investigated ameliorating effects of yellow chaste weed (YCW) (Helichrysum arenarium) extract and its components, apigenin and galangin, on blue light-irradiated HaCaT cells. In this study, we found that YCW extract improved the reduced proliferation of HaCaT cells induced by blue light-irradiation and reduced blue light-induced produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 89 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…Hence, Nar could effectively inhibit UVB‐induced apoptosis of HaCaT cells and promote cell proliferation. Cap, an irritating natural compound, can activate TRPV1, increase intracellular calcium concentration, and activate various apoptosis signaling pathways, thereby inducing apoptosis and cell cycle arrest of HaCaT cells (Park et al., 2022). We showed that treatment with the TRPV1 activator Cap inhibited HaCaT cell proliferation and promoted apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, Nar could effectively inhibit UVB‐induced apoptosis of HaCaT cells and promote cell proliferation. Cap, an irritating natural compound, can activate TRPV1, increase intracellular calcium concentration, and activate various apoptosis signaling pathways, thereby inducing apoptosis and cell cycle arrest of HaCaT cells (Park et al., 2022). We showed that treatment with the TRPV1 activator Cap inhibited HaCaT cell proliferation and promoted apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of antitumour activity of H. arenarium against transplanted sarcoma 45 while using immortelle extract was also indicated (Grinev et al, 2016). The extract of H. arenarium and its active components apigenin and galangin showed a significant protective effect on skin cells exposed to blue light (Park et al, 2022). Pospelov et al (2019) studied the biological activity of the native immortelle extract and its fraction with and without lectins in inhibiting the germination of teliospores Ustilago nuda.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al [4] demonstrated the ability of phenolic compounds to prevent the negative effects on the skin of blue light, also known as high-energy visible (HEV) light. Particularly, they studied the protective effects of yellow chaste weed (YCW) (Helichrysum arenarium) extract and its main components, apigenin and galangin, on HEV light-irradiated HaCaT keratinocytes from human skin.…”
mentioning
confidence: 99%